Teaching Strategies in English Extracurricular Activities at SMAN 85 Jakarta - Delia Mapela; Theresia Arianti (Foremost Journal, 2024)
Teaching strategies is one of the things that must be a concern for teachers, especially language teachers. Unfortunately, it is not uncommon for teachers to ignore this in the learning process. This can be seen from the way teachers choose teaching strategies which are sometimes not appropriate to the skills to be taught. This study included a participant which is a teacher from English Club at SMAN 85 Jakarta. In conducting the study, the researcher applied a qualitative method with a case study. The researcher used observation form and interviews as the instruments of this study. The results show that the most used teaching strategy in English Club at SMAN 85 Jakarta is direct learning strategy, while the least used teaching strategy is bottom-up strategy. The researcher also found that the reason for the teacher choosing a teaching strategy is mostly for the students to easily understands the concepts of the material used in the teaching strategies.